FAKTOR-FAKTOR PENENTU AUDIT DELAY DI INDONESIA - Handarudigdaya Jalanidhi Kuncaratrah (Universitas Jember, 2019)
This study aims to examine the determinants of audit delay in Indonesia, using Meta Analysis. Where Meta analysis is a standard statistical method that serves to synthesize results from individual studies that have